PLGA and PLLA nanoparticles encapsulating microparticles provide sequential release of three NSAID drugs - Yeo, Ryan Eng Wan (2016)
Drug delivery systems (DDSs) are versatile vessels, capable of carrying dyes, proteins, drugs and chemicals and delivering them at targeted sites, improving patient compliance, drug stability and potency, while reducing physiological fatigue from frequent high doses, infection, as well as the delivery of one or more potentially incompatible drug in a single dose.